1984
DOI: 10.4319/lo.1984.29.2.0340
|View full text |Cite
|
Sign up to set email alerts
|

Underwater radiant energy absorbed by phytoplankton, detritus, dissolved organic matter, and pure water

Abstract: The spectral irradiance distribution at five stations on lakes and at sea was measured with a portable underwater spectral irradiance meter. Chlorophyll a concentration and the absorption coefficient of the water were concurrently measured. From measured spectral irradiance distributions, radiant energy absorbed per unit volume was computed. At these stations, the effect of upward irradiance on total quanta absorbed by the water was negligibly small for all layers. The relative contributions of phytoplankton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 13 publications
0
64
0
1
Order By: Relevance
“…Vários estudos neste campo foram feitos, destacando-se Grobbelaar & Stegmann (1976), Junk et al (1981, Ribeiro (1983), Kishino et al (1984). 0 material em suspensão também preocupa no que tange ao assoreamento contínuo do lago formado.…”
Section: Introductionunclassified
“…Vários estudos neste campo foram feitos, destacando-se Grobbelaar & Stegmann (1976), Junk et al (1981, Ribeiro (1983), Kishino et al (1984). 0 material em suspensão também preocupa no que tange ao assoreamento contínuo do lago formado.…”
Section: Introductionunclassified
“…In several studies, using a number of approaches, the absorption spectra of particulate material from natural waters have been partitioned into two components: 1) the absorption by phytoplankton pigments, and 2) the absorption by what has been classified as "organic detritus" (e.g., Kiefer and SooHoo, 1982;Kishino et aL., 1984;Maske and Haardt, 1987). Spectrally, these two operational classes of organic chromophoresare quite different.…”
Section: Metals Release and Surface Alterationmentioning
confidence: 99%
“…Measurement of the spectral absorption coefficient for suspended particles in seawater has provided useful information since its introduction by Yentsch (1960), who has shown that this measurement can be quickly made using samples concentrated on glassfiber filters and a scanning spectrophotometer (see also Kiefer and SooHoo 1982;Kishino et al 1985;Mitchell and Kiefer 1988). In this technique, the particle absorption coefficient, a,(X) (units given in list of symbols), is computed from the difference between the optical density of a filter that contains suspended particles and a blank filter.…”
mentioning
confidence: 99%
“…Absorption by materials other than phytoplankton (e.g. detritus, bacteria, and dis-1500 solved substances) can also be variable, and there is as yet much discussion concerning the identity and origin of these materials (Kishino et al 1984;Smith and Baker 1978).…”
mentioning
confidence: 99%
See 1 more Smart Citation